PENINGKATAN KEMAMPUAN GARAP CIBLON IRAMA DADI DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA MAHASISWA SEMESTER II TAHUN AKADEMIK 2017/2018 - Sosodoro, Bambang (Acintya, 2019)
This class action research was conducted to improve the ability of students in kendangan ciblon irama dadi in Karawitan Surakarta II. The mastery of kendangan ciblon irama dadi is considered very important for it is the foundation for kendangan ciblon irama wiled in the form of inggah ladrang, kethuk 4, and kethuk 8 in the next course. Kendangan ciblon irama dadithat are emphasized are gambyongan ciblon which has a high complexity. Therefore,it needs more attention. So far, there are still many problems encountered in the learning process of the course, especially in mastering kendangan ciblonduring the middle semester, namely semester III, IV, IV. The problems include the scheme of kendangan, sekaran ciblongambyongan and wiledan. It may happen because most sudents do not master well the ciblon irama dadi at the second semester. It needs an appropriate learning method. In order to increase the students’ abilities in kendangan ciblon irama dadi semester II, during this time, the method of speech, drill and demonstration seem insufficient to overcome the problem, so that it is necessary to use another method namely the Stad Type Cooperative Learning Model. This method is in fact very effective and useful to improve the students’ practical skills. This is indicated by an increase in group learning activities and a more live class and the good student achievement.Keywords: learning, ability, ciblon